2003
DOI: 10.1016/s0006-2952(03)00540-9
|View full text |Cite
|
Sign up to set email alerts
|

Connexins and apoptotic transformation

Abstract: We examined the influence of connexin (Cx) expression on the development of apoptosis in HeLa parental cells (coupling deficient cell line) and HeLa cells expressing wild-type Cx43 and Cxs fused with enhanced green fluorescent protein (EGFP). EGFP was attached to the C-terminus of Cx32 and Cx43, Cx32-EGFP and Cx43-EGFP, respectively, and to the N-terminus of Cx32, EGFP-Cx32. All fusion proteins assembled into junctional plaques (JPs) at areas of cell-cell contact, but only the C-terminal fusion proteins formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 86 publications
(112 reference statements)
5
67
0
Order By: Relevance
“…In addition, various Cx26 mutants that are linked to Vohwinkel syndrome and PPK have been reported to exhibit dominant-negative and transdominant effects on other connexins, including Cx30 and Cx43 Marziano et al, 2003;Rouan et al, 2001). V37E Cx30 might exhibit these effects on coexpressed wild-type Cx30, Cx26 and Cx43, although, it is also possible that V37E-mutant expressing cells undergoing apoptosis internalize these connexins, as has been reported for Cx43 (Kalvelyte et al, 2003).…”
Section: The Loss-of-function V37e Mutant Linked To Clouston and Kidmentioning
confidence: 68%
“…In addition, various Cx26 mutants that are linked to Vohwinkel syndrome and PPK have been reported to exhibit dominant-negative and transdominant effects on other connexins, including Cx30 and Cx43 Marziano et al, 2003;Rouan et al, 2001). V37E Cx30 might exhibit these effects on coexpressed wild-type Cx30, Cx26 and Cx43, although, it is also possible that V37E-mutant expressing cells undergoing apoptosis internalize these connexins, as has been reported for Cx43 (Kalvelyte et al, 2003).…”
Section: The Loss-of-function V37e Mutant Linked To Clouston and Kidmentioning
confidence: 68%
“…Apoptotic index was further quantified by acridine orange/ethidium bromide uptake, as previously reported (24). Cells treated as described above were stained by using acridine orange (final 25 g/ml) and ethidium bromide (final 25 g/ml) mixture for 10 min, and then cells were photographed (ϫ100).…”
Section: Methodsmentioning
confidence: 99%
“…The GJ allows material less than 1 kDa in molecular weight to pass directly between the two adjacent cells. It has been demonstrated that GJs mediate GJ intercellular communication (GJIC), which plays important roles in the processes of cell growth and development (Li et al, 2010), the regulation of cell proliferation and apoptosis, and in the synchronization of cell activity, which is necessary to maintain a stable intracellular environment (Huang et al, 2001;Kalvelyte et al, 2003). However, whether GJ functional changes can influence the hepatotoxicity of TNF-α has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%